„Ich grolle nicht” w „Cudzoziemce” Marii Kuncewiczowej. O pieśni z perspektywy interdyscyplinarnej - Sokalska, Małgorzata (Poznańskie Towarzystwo Przyjaciół Nauk, 2014)
The paper focuses on the song as a syncretic, literary-musical genre. The appearance of song quotes in a novel (Cudzoziemka by Maria Kuncewiczowa) represents an interesting case, which may nevertheless be examined from purely literary perspective. However, a more profound interdisciplinary reading, which combines the elements of analysis of a piece of prose and a piece of music, enables a better interpretation of this particular motif in the novel.
”ICH GROLLE NICHT” IN MARIA KUNCEWICZOWA’S „CUDZOZIEMKA”. ON THE SONG FROM AND INTERDISCIPLINARY PERSPECTIVE
Song is at once a literary and a musical genre, thus reminding one of the melic origins of poetry. It gained singular popularity in certain periods, while Romanticism was the high point in the development of genre of vocal lyric called the song. In view of its syncretic nature, song is an object of literary and musicological studies, yet they are seldom profoundly interdisciplinary, although the material makes it difficult to maintain unadulterated methodological approach. It does sometimes happen that limiting the range of analytical tools to only one of the disciplines proves insufficient. This is exactly the case with e.g. Maria Kuncewiczowa’s Cudzoziemka, where the quote from R. Schumann’s lied Ich grolle nicht to the text of H. Heine was utilised functionally in a manner that deserves greater attention. The analysis of the novel, supplemented with observations about the musical characteristic of the song, is more comprehensive than it would have been if only the tools of literary analysis had been used.
Keywords: SONG,; ROMANTIC LIED; ROMANTIC LYRIC; MUSICAL MOTIFS IN PROSE; PSYCHOLOGICAL NOVEL; LITERARY-MUSICAL STUDIES